Analyzing Travel Behavior by Using GPS-Based Activity Spaces and Opportunity Indicators. Issue 2 (3rd April 2018) - van Dijk, Justin; Krygsman, Stephan
ABSTRACT: An activity space is a spatial expression of individual spatial behavior that can play a role in visualizing and analyzing travel behavior. In this article, we use the data of a two-day tracking experiment to explore whether accessibility to opportunities as represented through activity spaces associate with different travel characteristics, including willingness to consider more sustainable modes of transport. Simultaneously, we draw attention to the question of how to represent activity spaces. Using data of 95 respondents, we introduce point-of-interest data as an indicator to represent the accessibility to opportunities within individual activity spaces and we analyze their relationship to the respondents' self-reported willingness to consider more sustainable modes of travel. The results indicate that there is an association between higher scores on the activity space opportunity indicators and the willingness to consider more sustainable modes of transport. Overall, the study shows the potential of using accessibility indicators derived from GPS-based activity spaces to gain insight into travel behavior.